Linkage engineering by harnessing supramolecular interactions to fabricate 2D hydrazone-linked covalent organic framework platforms toward advanced catalysis - Qian, Cheng (2021)
Covalent organic frameworks (COFs) are an emerging class of crystalline porous polymers with tailor-made structures and functionalities. To facilitate their utilization for advanced applications, it is crucial to develop a systematic approach to control the properties of COFs, including the crystallinity, stability, and functionalities. However, such an integrated design is challenging to achieve. Herein, we report supramolecular strategy-based linkage engineering to fabricate a versatile 2D hydrazone-linked COF platform for the coordination of different transition metal ions. Intra- and intermolecular hydrogen bonding as well as electrostatic interactions in the antiparallel stacking mode were first utilized to obtain two isoreticular COFs, namely COF–DB and COF–DT. On account of suitable nitrogen sites in COF–DB, the further metalation of COF–DB was accomplished upon the complexation with seven divalent transition metal ions M(II) (M = Mn, Co, Ni, Cu, Zn, Pd, and Cd) under mild conditions. The resultant M/COF–DB exhibited extended π-conjugation, improved crystallinity, enhanced stability, and additional functionalities as compared to the parent COF–DB. Furthermore, the dynamic nature of the coordination bonding in M/COF–DB allows for the easy replacement of metal ions through a postsynthetic exchange. In particular, the coordination mode in Pd/COF–DB endows it with excellent catalytic activity and cyclic stability as a heterogeneous catalyst for the Suzuki–Miyaura cross-coupling reaction, outperforming its amorphous counterparts and Pd/COF–DT. This strategy provides an opportunity for the construction of 2D COFs with designable functions and opens an avenue to create COFs as multifunctional systems.